Promotion of Physical Activity through Health Applications among Students of Selected Universities - a Preliminary Study - Lynn Smith; Cheryl-Ann Volkwyn (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2022)
Mobile health applications provide individuals with a mobile tool that can be tailored to meet various health needs and physical activity goals, which is particularly important during the Covid-19 pandemic and the associated social distancing protocols. The consequence that the pandemic has on the mental health of university students has prompted and increased the demand of physical activity interventions. The aim of this study was to determine the self-perceived effects of mobile health applications on physical activity participation among university students. Participants included students registered in one of the faculties at a university in Johannesburg. Data collection took place by means of an electronic questionnaire using Google Forms as a platform, completed by a sample of 192 students. The findings in the study reflected that majority of university students use health applications to increase physical activity levels or to track current activity levels. Participants also indicated that specific health applications were used to set goals, monitor progress and receive feedback. Aerobic activities proved to be the more popular type of physical activity in comparison to anaerobic activity. This study concluded that health applications can be used as a tool to facilitate and promote physical activity participation in the university student population.